Three thieves. Book 1, Tower of treasure - Chantler, Scott (Three thieves, 2010)
As an acrobat in a traveling circus, 14-year-old orphan Dessa Redd flies through the air with ease. Still, she is weighed down by troubling memories. But when her ragtag circus troupe pulls into the city of Kingsbridge, Dessa feels a tickle of hope. Maybe here in the royal city she will finally find her twin brother -- or the mysterious man who snatched him away when they were just children. Meanwhile, Topper, the circus juggler, recruits Dessa and the circus strongman, Fisk, for the job of robbing the royal treasury. Hungry and desperate, both agree, setting off a series of adventures that will take the three thieves from one end of the world to the other in search of Dessa's long-lost brother.